Enteromorpha Compressa, Gelidium pulchrum, Macro algae from Egypt Exhibit Potent Anticancer, Antioxidant and anti-inflammatory Activities - Faten mohmad Abou-Elella,; Mahgoub M Ahmed, (International Journal of Phytomedicine, 2015)
Over the past several decades, algae and their extracts have generated an enormous amount of interest in the pharmaceutical industry as a fresh source of bioactive compounds. The aim of this work was to evaluate anticancer, antioxidant and anti-inflammatory properties of absolute and aqueous (50%) methanol extracts of both Gelidium pulchrum and Enteromorpha compressa algae. In vitro cytotoxicity of the extracts was tested by MTT and trypan blue technique against two malignant cell lines (HeLa and EACC). The effect of methanol extracts on caspase-3 and Bax gene protein expression levels was evaluated as indicator of apoptosis induction in treated- Hela cells. The antioxidant activity was evaluated using three methods,(DPPH, Reducing power and ABTS) andanti-inflammatory activity measured by two systems (in vivo and in vitro). The obtained results showed that all studied extracts expressed signiﬁcant in vitro cytotoxic activity toward HeLa, and EACC cell lines. The data revealed up regulation of both Bax and caspase-3 protein expressions levels in treated-HeLa cell line. In DPPH assay aqueous MeOH extracts of Gelidium pulchrum exhibit maximum inhibition (IC50= 51±2.3). The highest reducing power was 179.3±4.7µg/mL GAE in aqueous MeOH extract of Gelidium pulchrum. The data also showed that all tested extracts have anti-nflammatory activity against carrgeenan induced paw oedema. While absolute MeOH extract of Gelidium pulchrum has maximum protection (71.7±1.7 %) in membrane stabilization test. Data obtained indicate the potential of these algal extracts for the antitumor through induction of apoptosis in cancer cells in addition to, the antioxidant and anti-inflammatory actions. This biological action is interesting for further isolation and identification of new natural anticancer and antioxidant compounds.